Development and Characterization of a Low-Fat Mayonnaise Salad Dressing Based on Arthrospira platensis Protein Concentrate and Sodium Alginate - Jorge Metri-Ojeda; Milena Ramírez-Rodrigues; Lizbeth Rosas-Ordoñez; Diana Baigts-Allende (Applied Sciences, 2022)
The food industry is constantly reformulating different foods to fulfill the demands of the consumers (natural ingredients and good sensory quality). The present work aimed to produce low-fat mayonnaises using 30.0, 22.5, and 15.0% oil, 1% soy protein isolate (SPI) or spirulina (Arthrospira platensis) protein concentrate (SPC), and 2% sodium alginate. The physical properties (thermal stability, rheological behavior, and particle size), the sensory attributes (appearance, texture, taste, and acceptability), the purchase probability, and amino acid availability (after a simulated digestion) were evaluated. The mayonnaises demonstrated good thermal stability (>90%) using 22.5 and 15% oil, all products showed shear-thinning behavior and a consistency index of 20–66 Pa·s. The reduction of oil from 30 to 15% increased the particle size from 6–9 µm to 10–38 µm. The most acceptable product was the formulated with SPI and 22.5% oil (8.3 of acceptability and 79% of purchase probability). Finally, the addition of proteins improved the total essential amino acids compared to a commercial product (28 and 5 mg/25 g, respectively). In summary, it was possible to obtain well accepted products with high purchase probability using low concentrations of oil and vegetable proteins.